Ujaran Kebencian Terhadap Jokowi pada Masa Pandemi Covid-19: Studi Kasus Twitter - Wahyu Maulana; Mulyadi Mulyadi (Jurnal Linguistik Komputasional, 2021)
The purpose of this study is to analyze what form of hate speech is aimed at Jokowi during Covid-19 pandemic in Indonesia by using speech act theory. The researcher uses Twitter developer account and Python for collecting data in this study. Through the analyzed data, it’s shown that 5% of the tweets containing “jokowi” is hate speech. The analysis is aimed to get what form of hate speech in the tweets such as: insult, defamation , blasphemy, unpleasant acts, provocation, and hoax. At the end of the study, the researcher finds that the most hate speech aimed at Jokowi is unpleasant acts.